High-rigidity aluminum-based alloy and method for producing the same
By uniformly dispersing fine titanium boride particles in aluminum-based alloys through insulating mixing and additive manufacturing, the alloy achieves high rigidity with improved machinability and prevents cutting tool damage.
Patent Information
- Application Number
- JP2023092456
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
AI Technical Summary
High-rigidity aluminum-based alloys face issues during machining as coarse borides with high hardness disperse in the matrix, leading to cutting tool destruction.
A method involving mixing aluminum or aluminum alloy powder with fine titanium boride particles in a metal container using an insulating spacer to prevent static electricity, followed by additive manufacturing to uniformly disperse the borides, maintaining small particle sizes and uniform distribution.
The method produces a highly rigid aluminum-based alloy that can be easily machined while preserving high rigidity, preventing cutting tool breakage and ensuring uniform dispersion of titanium boride particles.
Smart Images

Figure 2024174565000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-rigidity aluminum-based alloy and a method for producing the same. [Background technology]
[0002] In order to reduce the weight of components, devices, and even vehicles, research is being conducted to replace conventional iron-based components with light metal components such as Al-based alloys and Mg-based alloys. This trend is not limited to simple cases and housings, but extends to functional components that require wear resistance and sliding properties, such as cylinder liners for internal combustion engines (reciprocating engines) in the case of automotive components.
[0003] In such Al-based alloys, research and development is being conducted on dispersing compound particles such as borides, which have a high Young's modulus, in order to increase the rigidity of the alloys.
[0004] For example, Patent Document 1 describes a method for producing an aluminum-based composite material in which an aluminum alloy substrate is infiltrated into a preform formed of at least one of reinforcing materials, ceramic fibers and ceramic particles, the aluminum alloy containing 1% to 6% by weight of magnesium by weight and 3% to 20% by volume of titanium boride by volume, and the aluminum alloy is melted at a temperature of 750°C to 850°C and infiltrated into the preform at a pressure of 5 MPa to 50 MPa.
[0005] Patent Document 2 describes a high-strength Al alloy characterized in that at least one of TiB-based particles containing Fe or TiB-based particles containing Fe and Si is dispersed in an Al-based matrix.
[0006] Patent Document 3 describes a method for producing a ceramic-reinforced aluminum alloy metal matrix composite, which comprises a step of combining molten aluminum with a molten flux in an inert atmosphere substantially free of oxygen and moisture.
[0007] Patent Document 4 describes a method for producing an aluminum-based product, the method comprising: (a) dispersing a metal powder in a bed, the metal powder comprising ceramic metal particles, the ceramic metal particles comprising a ceramic material dispersed within an aluminum material; (b) selectively heating a portion of the metal powder to a temperature above the liquidus temperature of the aluminum material; (c) forming a molten pool; (d) cooling the molten pool at a cooling rate of at least 1000° C. / sec; and (e) repeating steps (a) to (d) until the aluminum-based product is completed, the aluminum-based product comprising one or more ceramic phases, the aluminum-based product comprising 1 to 30 volume % of the one or more ceramic phases dispersed within an aluminum-based matrix. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2002-115017 A [Patent Document 2] Japanese Patent Application Publication No. 7-268510 [Patent Document 3] Special Publication No. 11-502570 [Patent Document 4] Special Publication No. 2018-512507 Summary of the Invention [Problem to be solved by the invention]
[0009] However, in high-rigidity aluminum-based alloys (high-rigidity Al-based alloys), the highly hard and coarse borides dispersed in the matrix made of Al or Al alloy (Al-based matrix) could destroy cutting tools during machining such as cutting.
[0010] Therefore, an object of the present invention is to provide a highly rigid Al-based alloy that can be easily machined, and a method for producing the same. [Means for solving the problem]
[0011] The cause of the coarsening of borides in high-rigidity Al-based alloys is the powder of Al or Al alloy that constitutes the matrix of the high-rigidity Al-based alloy and the small particle size of borides, for example, titanium boride (TiB) with an average particle size of 10 μm or less. 2 ) powder to obtain a homogeneous mixture; and when the powder mixture is melted, the originally fine titanium boride particles aggregate and bond together, becoming larger.
[0012] The inventors of the present invention have investigated various means for solving the above problems, and as a result, have found that a raw material containing Al or Al alloy powder and titanium boride having a small particle size is placed in a metal container, and the metal container is placed on a stirrer via an insulating spacer, and stirred and mixed, whereby TiB2 having a small particle size is produced in the metal container containing the raw material. 2 It was found that the TiB particles could be uniformly adsorbed onto the surface of Al or Al alloy particles. This is because the metal container containing the raw materials and the agitator are insulated from each other, and the static electricity generated in the metal container during mixing of the raw materials has no way to escape. 2 This is because electrostatic adhesion occurs between the Al particles and the Al or Al alloy particles. Furthermore, the inventors have found that by processing the mixed powder thus prepared by the additive manufacturing method, an Al-based matrix and fine TiB particles uniformly dispersed in the matrix are obtained. 2 The present invention has been accomplished by discovering that a high-rigidity Al-based alloy containing the above can be produced.
[0013] That is, the gist of the present invention is as follows. (1) A high-rigidity aluminum-based alloy comprising a matrix made of aluminum or an aluminum alloy and titanium boride dispersed in the matrix, the titanium boride content being 10 volume % to 50 volume % relative to the total volume of the high-rigidity aluminum-based alloy, and the titanium boride having a circle-equivalent average particle size of 0.01 μm to 10 μm with a relative standard deviation of 1 or less, as measured in an SEM image. (2) A high-rigidity aluminum-based alloy according to (1), in which the titanium boride has an average circle-equivalent grain size of 0.01 μm to 5 μm with a relative standard deviation of 0.8 or less, as measured by an SEM image. (3) A method for producing a high-rigidity aluminum-based alloy, comprising: (i) a step of placing raw materials containing a powder of aluminum or an aluminum alloy and a powder of titanium boride in a metal container, wherein the content of titanium boride is 10% by volume to 50% by volume relative to the total volume of the high-rigidity aluminum-based alloy, and the titanium boride has a circle-equivalent average particle size of 0.01 μm to 10 μm as measured by a SEM image; (ii) a step of placing the metal container containing the raw materials in step (i) in a stirrer via an insulating spacer, stirring and mixing the raw materials to obtain a mixed powder; and (iii) a step of processing the mixed powder obtained in step (ii) by an additive manufacturing method to obtain a high-rigidity aluminum-based alloy. Effect of the Invention
[0014] The present invention provides an easily machineable, highly rigid Al-based alloy and a method for producing the same. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a schematic diagram showing an example of a state in which a metal container 1 is placed on a stirrer 3 via an insulating spacer 2 in step (ii) of the method of the present invention. [Diagram 2]1A is a schematic diagram showing the state of Al or Al alloy particles 4 and TiB2 particles 5 in a mixed powder obtained by a conventional method, (B) the state of Al or Al alloy particles 4 and TiB2 particles 5 when the mixed powder obtained by a conventional method is subjected to additive manufacturing, and (C) the state of Al or Al alloy particles 4 and TiB2 particles 5 in a mixed powder obtained by the method of the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing an example of an apparatus for carrying out an additive manufacturing method using a PBF method. [Figure 4] 1 is a photograph of the mixed powder obtained in step (ii) of Example 1, observed by SEM. [Diagram 5] 1 shows SEM photographs of an Al-based alloy (A) obtained in Example 1 and an Al-based alloy (B) obtained in Comparative Example 1. [Figure 6] 1 shows SEM photographs of an Al-based alloy (A) obtained in Example 1 and an Al-based alloy (B) obtained in Comparative Example 1 for calculating particle size distribution (standard deviation). [Figure 7] 1 is a graph showing the machinability of Al-based alloys of Examples 1 to 5 and Comparative Examples 2 to 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Preferred embodiments of the present invention will now be described in detail. In this specification, the features of the present invention will be described with reference to the drawings as appropriate. In the drawings, the dimensions and shapes of each part are exaggerated for clarity, and the actual dimensions and shapes are not accurately depicted. Therefore, the technical scope of the present invention is not limited to the dimensions and shapes of each part shown in these drawings. The high-rigidity aluminum-based alloy and its manufacturing method of the present invention are not limited to the following embodiments, and can be embodied in various forms with modifications and improvements that can be made by those skilled in the art within the scope of the gist of the present invention.
[0017] The present invention relates to a high-rigidity aluminum-based alloy comprising a matrix made of aluminum or an aluminum alloy and titanium boride dispersed in the matrix, the titanium boride content, as well as the average grain size and relative standard deviation thereof, being specified.
[0018] Here, the high-rigidity aluminum-based alloy (high-rigidity Al-based alloy) of the present invention has a structure in which fine titanium borides are uniformly dispersed in an Al-based matrix.
[0019] A wide range of aluminum alloys can be used as the matrix of the high-rigidity Al-based alloy of the present invention, including aluminum alloys that typically contain 4% to 24% by mass of silicon relative to the total mass of the aluminum alloy, and aluminum-based alloys in general.
[0020] The titanium boride uniformly dispersed in the Al-based matrix of the high-rigidity Al-based alloy of the present invention has the chemical formula TiB 2 It is a diboride represented by the formula:
[0021] The titanium boride contained in the high-rigidity Al-based alloy of the present invention has a regular crystal structure and is a compound in which the constituent atoms are strongly bonded, so that the Young's modulus, which directly reflects the bonding force, is extremely high. In addition, since titanium boride is thermodynamically stable in an Al alloy, it does not undergo crystallographic changes due to the reaction between titanium boride and an Al-based matrix, such as the intrusion or substitution of different atoms or the formation of other complex compounds. As a result, titanium boride maintains a strong bonding force even in an Al alloy, does not change with its high Young's modulus, and can fully exert its excellent properties as a reinforcing particle that contributes to the high rigidity of an Al-based alloy. Therefore, the Al-based alloy of the present invention can have an extremely high Young's modulus, for example, a Young's modulus of typically 90 GPa to 160 GPa.
[0022] The average particle size of titanium boride is usually 0.01 μm to 10 μm, preferably 0.01 μm to 5 μm, and more preferably 0.01 μm to 1 μm, as the average circle-equivalent particle size according to an SEM image. The relative standard deviation of the particle size of titanium boride is usually 1 or less, preferably 0.8 or less. Here, the relative standard deviation (RSD) is the value obtained by dividing the standard deviation by the average value (i.e., the standard deviation of the particle size / average particle size). The lower limit of the relative standard deviation is not limited, because it is preferable that the particle size is uniform.
[0023] The average circle-equivalent particle size in SEM images of titanium boride can be determined by first taking three BSE-SEM images (backscattered electron images) of the high-rigidity Al-based alloy to be measured, then randomly selecting 200 or more titanium borides from each image, calculating the area of each selected titanium boride, calculating the circle-equivalent diameter from the calculated area, and taking the arithmetic mean value from the calculated circle-equivalent diameters. The standard deviation σ can be calculated based on the obtained circle-equivalent average particle size.
[0024] If the average particle size of titanium boride is too small, for example, less than 0.01 μm, it inhibits the movement of dislocations and increases the macro strength. On the other hand, if the average particle size of titanium boride is too large, for example, more than 10 μm, it becomes difficult to machine. Therefore, when the average particle size of titanium boride is within the above range, the stress applied to the cutting tool in cutting the high-hardness titanium boride during processing of the high-rigidity Al-based alloy is dispersed, the breakage of the cutting tool is reduced, and the machinability is improved while maintaining high rigidity.
[0025] Furthermore, by having the relative standard deviation of titanium boride within the above range, i.e., by having the grain size of titanium boride be uniform, when machining a high-rigidity Al-based alloy, the stress applied to the cutting tool in cutting the high-hardness titanium boride is dispersed, reducing breakage of the cutting tool and improving machinability while maintaining high rigidity.
[0026] The content of titanium boride is usually 10 volume % to 50 volume %, and preferably 10 volume % to 30 volume %, relative to the total volume of the high-rigidity Al-based alloy.
[0027] In the present invention, even if the content of titanium boride is within the above range, the titanium boride does not cause aggregation or coalescence of the borides, and can exhibit sufficient mechanical properties, particularly high rigidity, in a high-rigidity Al-based alloy.
[0028] Therefore, the high-rigidity Al-based alloy of the present invention exhibits sufficient mechanical properties, particularly high rigidity, due to the presence of titanium boride, and furthermore, due to the fineness of the titanium boride and the small crystal grains of the Al-based matrix, it can be easily cut in the cutting process without destroying the cutting tool.
[0029] In addition to titanium boride, the high-rigidity Al-based alloy of the present invention may contain one or more other elements, such as silicon, magnesium nickel, cobalt, chromium, molybdenum, carbon, manganese, and compounds thereof, such as borides, depending on the components required in the final high-rigidity Al-based alloy.
[0030] Furthermore, the present invention also relates to a method for producing the high-rigidity Al-based alloy of the present invention described above. That is, the present invention relates to a method for producing a high-rigidity aluminum-based alloy, comprising the steps of (i) placing raw materials, including a powder of aluminum or an aluminum alloy and a powder of titanium boride having a specified content and average particle size, in a metal container, (ii) installing the metal container containing the raw materials in step (i) in a stirrer via an insulating spacer and stirring and mixing to obtain a mixed powder, and (iii) treating the mixed powder obtained in step (ii) by an additive manufacturing method to obtain a high-rigidity aluminum-based alloy.
[0031] Each of steps (i) to (iii) will be explained below.
[0032] In the step (i), the powder made of an aluminum alloy may be an aluminum alloy powder containing silicon, as described above, in an amount of usually 4% by mass to 24% by mass relative to the total mass of the aluminum alloy.
[0033] The average particle size of the powder made of aluminum or an aluminum alloy is not limited, but is usually 15 μm to 100 μm, and preferably 20 μm to 60 μm, as measured by laser diffraction, for example.
[0034] By setting the average particle size of the powder made of aluminum or an aluminum alloy within the above range, it is possible to easily and uniformly mix the powder made of aluminum or an aluminum alloy with titanium boride in the step (ii) described below.
[0035] The average particle size of the titanium boride powder, as the circle-equivalent average particle size in the SEM image described above, is usually 0.01 μm to 10 μm, preferably 0.01 μm to 5 μm, and the relative standard deviation of the particle size of the titanium boride powder is usually 1 or less, preferably 0.8 or less.
[0036] By making the average particle size of the titanium boride powder within the above range, it is possible to easily and uniformly mix the aluminum or aluminum alloy powder with the titanium boride in the step (ii) described below. Also, since the average particle size of the titanium boride powder is almost the same as the average particle size of the titanium boride in the high-rigidity Al-based alloy obtained by the step (iii) described above or below, the finally obtained high-rigidity Al-based alloy has high rigidity and machinability, which are the effects of the particle size of the titanium boride described above.
[0037] The ratio of the aluminum or aluminum alloy powder and the titanium boride powder is adjusted to usually be 10 volume % to 50 volume %, preferably 10 volume % to 30 volume %, relative to the total volume of the high-rigidity Al-based alloy so as to obtain the high-rigidity Al-based alloy described above.
[0038] The raw materials may contain one or more other elements, such as silicon, magnesium, nickel, cobalt, chromium, molybdenum, carbon, manganese, etc., depending on the components required in the final high-rigidity Al-based alloy.
[0039] Examples of metal containers include those made of iron and stainless steel.
[0040] The order, temperature and method of storing each powder, i.e., the powder made of aluminum or an aluminum alloy, the powder of titanium boride, and optionally the powder containing one or more other elements, in the metal container are not limited, and any storing means known in the art can be used. For example, when the raw material contains a powder containing one or more other elements, the powder made of aluminum or an aluminum alloy and the powder of titanium boride may be stored in a metal container at 20°C to 40°C, and then the powder containing one or more other elements may be stored, or the powder made of aluminum or an aluminum alloy and the powder containing one or more other elements may be stored in a metal container and then the titanium boride powder may be mixed, or the powder made of titanium boride and the powder containing one or more other elements may be stored in a metal container and then the powder made of aluminum or an aluminum alloy may be stored, or all the powders may be stored in a metal container at the same time.
[0041] In step (ii), the insulating spacer is a device (spacer) made of a material that does not conduct electricity, for insulatingly connecting the metal container and the stirrer. The insulating spacer is not limited, and any insulating spacer known in the art can be used. Examples of the insulating spacer include spacers made of polystyrene foam, rubber, plastics such as polyethylene, polyester, epoxy, melamine, phenol, polyurethane, and inorganic materials such as ceramics and glass.
[0042] The stirrer is not limited, and any stirrer known in the art can be used. Examples of the stirrer include a V-type mixer (V-type powder mixer), a ball mill, and a vibration mill.
[0043] FIG. 1 shows a schematic diagram of an example of how a metal container 1 is placed on a stirrer 3 via an insulating spacer 2 in step (ii) of the method of the present invention.
[0044] The stirring conditions are not limited, and for example, mixing is usually performed at 18° C. to 26° C. for 10 minutes to 60 minutes.
[0045] The metal container containing the raw materials is placed on a stirrer via an insulating spacer and stirred, whereby TiB2 particles with small particle size are mixed in the metal container containing the raw materials. 2 The particles can be uniformly adsorbed onto the surface of Al or Al alloy particles. This is because the metal container containing the raw materials is insulated from the agitator, and the static electricity generated in the metal container during the mixing of the raw materials has nowhere to escape, and the static electricity causes the TiB 2 This is because electrostatic adhesion occurs between the particles and the Al or Al alloy particles.
[0046] FIG. 2 shows the Al or Al alloy particles 4 and TiB in the mixed powder obtained by the conventional method (a mixing method without using an insulating spacer). 2 The state of the particles 5 (A), the state of the Al or Al alloy particles 4 and TiB when the mixed powder obtained by the conventional method is additively manufactured. 2 The state of the particles 5 (B), and the state of the Al or Al alloy particles 4 and TiB in the mixed powder obtained by the method of the present invention. 2 The state of particle 5 (C) is shown diagrammatically.
[0047] As shown in Figure 2A, in the mixed powder obtained by the conventional method, TiB 2 Particle 5 is agglomerated or has poor flowability and cannot be spread. 2 When the particles 5 are subjected to additive manufacturing while being in an agglomerated state, TiB 2 On the other hand, as shown in FIG. 2C, in the mixed powder obtained by the method of the present invention, TiB 2 Even if the content of particle 5 is large, TiB 2 The TiB particles 5 can be uniformly adsorbed on the surface of the Al or Al alloy particle 4. 2 The particles 5 do not become coarse even when subjected to additive manufacturing.
[0048] In the step (iii), the additive manufacturing method is a method in which the raw alloy powder is laid out layer by layer, and then a laser or electron beam is irradiated onto the layer based on slice data converted from 3D data to melt and solidify only specific areas, and this process is repeated to form the pre-heat-treated alloy without a mold.
[0049] In the additive manufacturing method, the mixed powder can be rapidly heated, convectively stirred, and rapidly cooled. In the additive manufacturing method, the cooling rate during additive manufacturing, that is, the cooling rate at which a specific portion is melted by irradiating a laser or an electron beam and then solidified, is usually 10,000 K / sec or more. In order to set the cooling rate during additive manufacturing within the above range, cooling can be performed using, for example, argon gas or nitrogen gas.
[0050] Additive manufacturing methods include, for example, Powder Bed Fusion (PBF).
[0051] PBF is a method in which mixed powder is spread out, and the part to be shaped is irradiated with a laser or electron beam, causing it to melt, solidify, and layer up to form an alloy.
[0052] In PBF, alloy precursors that have been melted by irradiation with a laser or electron beam can be rapidly cooled, typically at a rate of 10,000 K / sec or more, to produce the alloy.
[0053] Fig. 3 is a schematic diagram of an example of an apparatus for implementing additive manufacturing by the PBF method. In Fig. 3, first, mixed powder 6 loaded in a raw material container is pushed up in a cover 12 for creating a vacuum atmosphere, and the pushed-up mixed powder 6 is spread out by a blade 7. Next, a laser or electron beam 9 is irradiated by a laser or electron beam generator 8 onto the mixed powder 6 spread out by the blade 7. When the mixed powder 6 is irradiated with the laser or electron beam 9, the powders in the mixed powder 6 are fused and bonded together to form an Al-based alloy 10 on a base plate 11. These steps are repeated while lowering the base plate 11 (additive manufacturing), and the Al-based alloy 10 is molded.
[0054] For additive manufacturing, equipment known in the art can be used, such as, but not limited to, the 280HL manufactured by SLM Solutions.
[0055] In the present invention, by using the additive manufacturing method, the cooling rate after powder melting can be increased, that is, the grain (crystal) growth time of titanium boride and the grain growth time of Al-based matrix can be shortened. Furthermore, the titanium boride particles have a pinning effect on the grains of the Al-based matrix, causing the Al-based matrix to be refined. Therefore, as a result of the synergistic effect of the grain refinement of titanium boride and Al-based matrix due to the shortening of the time until the material solidifies and the grain refinement of the Al-based matrix due to the pinning effect of the fine titanium boride, a high-rigidity Al-based alloy can be formed in which small grain borides are formed in the Al-based matrix with small grains, which achieves both high rigidity and high strength and also improves the elongation relative to strength. EXAMPLES
[0056] Several examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.
[0057] I. Examination of the raw material mixing process Example 1 An Al-based alloy was produced by the following steps (i) to (iii).
[0058] (i) Aluminum alloy powder containing 12 mass% silicon based on the total mass of the aluminum alloy and titanium boride powder (average particle size (SEM): 0.1 μm, 20 volume% based on the total volume of the Al-based alloy) were placed in a stainless steel container.
[0059] (ii) The stainless steel container containing the raw materials in step (i) was placed in a vibration mill (container installation location: stainless steel) via an insulating spacer, and the mixture was stirred and mixed at 25°C for 30 minutes to obtain a mixed powder.
[0060] (iii) The mixed powder obtained in step (ii) was processed (melted and solidified) by additive manufacturing to obtain an Al-based alloy. Lamination conditions Additive manufacturing machine: 3D Systems Preparation conditions: Build angle 90°, platform preheat 200°C, layer thickness 30μm Shape of the sculpture: 10mm x 10mm x 10mm Laser power: 225W (75% power) Laser scanning: 1200mm / s
[0061] Comparative Example 1 An Al-based alloy was obtained in the same manner as in Example 1, except that no insulating spacer was used (that is, the stainless steel container and the vibration mill were conductively connected).
[0062] The mixed powder obtained in step (ii) of Example 1 was observed by SEM. The results are shown in FIG. 4. Note that A and B in FIG. 4 are different magnifications. From FIG. 4, it was found that in the mixed powder obtained in step (ii) of Example 1, fine titanium boride 5 was uniformly adsorbed onto the Al particle surfaces. In Example 1, it was found that by insulatingly connecting the stainless steel container containing the raw material to the vibration mill, fine titanium boride 5 could be uniformly adsorbed onto the Al particle surfaces by electrostatic adsorption.
[0063] The Al-based alloys obtained in Example 1 and Comparative Example 1 were observed by SEM. The results are shown in Figure 5. It was found from Figure 5 that in the Al-based alloy of Example 1 (Figure 5A), titanium boride 5 was uniformly dispersed in the Al-based matrix, whereas in the Al-based alloy of Comparative Example 1 (Figure 5B), coarse particles of titanium boride 5 were present in the Al-based matrix.
[0064] Next, the circle-equivalent average grain size was calculated from the SEM photographs of the Al-based alloys obtained in Example 1 and Comparative Example 1. The results are shown in Tables 1 and 2 and Fig. 6 (A: Example 1, B: Comparative Example 1).
[0065] [Table 1]
[0066] [Table 2]
[0067] From Tables 1 and 2 and FIG. 6, it was found that in Example 1, the average particle size of titanium boride had a small standard deviation, that is, an excellent (narrow) particle size distribution.
[0068] Furthermore, when the Young's modulus of the Al-based alloy of Example 1 was measured, it was found to have a Young's modulus of 104 GPa, whereas Al has a Young's modulus of approximately 70 GPa.
[0069] Therefore, it was found that the Al-based alloy of the present invention can maintain fine titanium boride even if it contains 20 volume % of titanium boride, and can achieve both high rigidity and machinability. On the other hand, in the case of the Al-based alloy of Comparative Example 1, the titanium boride aggregates and becomes coarse, making it impossible to machine and becoming the starting point of fracture.
[0070] II. Study of the average particle size of titanium boride Examples 2 to 5 An Al-based alloy was obtained in the same manner as in Example 1, except that the average particle size (SEM) of titanium boride was changed to 0.01 μm (Example 2), 1 μm (Example 3), 5 μm (Example 4), or 10 μm (Example 5).
[0071] Comparative Examples 2 to 4 An Al-based alloy was obtained in the same manner as in Example 1, except that the average particle size (SEM) of titanium boride was changed to 0.001 μm (Comparative Example 2), 25 μm (Comparative Example 3), or 30 μm (Comparative Example 4).
[0072] The machinability of the Al-based alloys of Examples 1 to 5 and Comparative Examples 2 to 4 was evaluated. The results are shown in Figure 7. The higher the machinability, the better the result.
[0073] FIG. 7 shows that in an Al-based alloy in which the dispersibility of titanium boride is improved, the machinability can be improved by setting the average grain size of titanium boride by SEM to 0.01 μm to 10 μm, preferably 0.1 μm to 1 μm. [Explanation of symbols]
[0074] 1. Metal container, 2. Insulating spacer, 3. Stirrer, 4. Aluminum or aluminum alloy, 5. Titanium boride, 6. Mixed powder, 7. Blade, 8. Laser or electron beam generator, 9. Laser or electron beam, 10. Al-based alloy, 11. Base plate, 12. Cover
Claims
1. A high-rigidity aluminum-based alloy comprising a matrix of aluminum or an aluminum alloy and titanium boride dispersed in the matrix, The content of titanium boride is 10% by volume to 50% by volume based on the total volume of the high-rigidity aluminum-based alloy; The average circle-equivalent particle size of titanium boride as measured by SEM imaging is 0.01 μm to 10 μm with a relative standard deviation of 1 or less. High-strength aluminum-based alloy.
2. 2. The high stiffness aluminum-based alloy according to claim 1, wherein the titanium boride has an average circle-equivalent grain size in a SEM image of 0.01 μm to 5 μm with a relative standard deviation of 0.8 or less.
3. A method for producing a high stiffness aluminum-based alloy, comprising the steps of: (i) A step of placing a raw material containing a powder of aluminum or an aluminum alloy and a powder of titanium boride in a metal container, wherein the content of titanium boride is 10% by volume to 50% by volume with respect to the total volume of the high-rigidity aluminum-based alloy, and the average circle-equivalent particle size of titanium boride according to a SEM image is 0.01 μm to 10 μm; (ii) a step of placing the metal container containing the raw materials in the step (i) on a stirrer via an insulating spacer and stirring and mixing the raw materials to obtain a mixed powder; and (iii) A step of processing the mixed powder obtained in the step (ii) by an additive manufacturing method to obtain a high-rigidity aluminum-based alloy. The method includes:
Citation Information
Patent Citations
High-strength al alloy and its production
JP1995268510A
tib▲Lower 2▼ Aluminum-alloy metal-matrix composite reinforced with fine-grained ceramics
JP1999502570A
Method for producing aluminum composite material
JP2002115017A
Aluminum alloy product and manufacturing method thereof
JP2018512507A
